Effects of a Cereal and Soy Dietary Formula on Rehabilitation of Undernourished Children at Ouagadougou, in Burkina Faso. (28th November 2011) - Douamba, Zoenabo; Martinetto, Marina; Pietra, Virginio; Pignatelli, Salavatore; Schumacher, Fabian; Nikiema, Jean-Baptiste; Simpore, Jacques
Abstract : The New Misola consists of millet soybean, peanut, vitamins, minerals, and industrial amylase. Our objective is to demonstrate that porridge made from local grains and legumes restores the nutritional balance of malnourished children. The study was carried on 304 malnourished children aged 6–48 months including 172 girls and 132 boys from Saint Camille Medical Centre. At the beginning, these malnourished children had a WHZ z -score of −3.10 and a WAZ z -score of −3.85, which reflected, according to WHO, a severe malnutrition. After eight weeks of nutritional rehabilitation, a normal WHZ of −1.41 was obtained. These children recovered more than those in a similar study performed in 2006 with the old formula of Misola. This study shows that malnutrition remains a public health problem in Burkina Faso. It should be necessary that public health services and the epidemiologists work in synergy with nutritionists and " nutrigenetics " in order to combat malnutrition efficiently.